A chemically-responsive bis-acridinium receptor. (1st March 2018) - Gosset, A.; Xu, Z.; Maurel, F.; Chamoreau, L.-M.; Nowak, S.; Vives, G.; Perruchot, C.; Heitz, V.; Jacquot de Rouville, H.-P.
Abstract : The recognition and the chemical-response properties of a bis-acridinium triphenylene receptor were investigated. Abstract : A dicationic receptor based on two acridinium moieties linked by a triphenylene spacer was studied in solution and in the solid state. Recognition moieties, namely acridiniums, were exploited to evidence a host–guest response of the receptor with electron rich guests. Upon addition of methoxide anions, the formation of the bis-acridane form of the receptor was observed. The chemical responsiveness of the receptor to these anions inhibits its recognition properties towards π-donor guests. In addition, the reversibility of the chemical response was demonstrated under acidic conditions.